A mental warm-up for athletes - Brewer, B. W.; Haznadar, A.; Katz, D.; Van Raalte, J. L.; Petitpas, A. J. (The Sport Psychologist, 2019)
The purpose of this research was to develop and evaluate a 5-min structured mental warm-up involving aspects of goal setting, imagery, arousal regulation, and positive self-talk. Results of a study that featured a pretest-posttest design with 101 male youth soccer players (Study 1) and a study that featured a repeated-measures experimental design with 29 female intercollegiate soccer players (Study 2) indicated that executing the mental warm-up was associated with significantly greater readiness to perform and to use mental skills to enhance performance. In Study 3, 30 male high school soccer players used the mental warm-up daily over a competitive season and rated it as acceptable (albeit less so than their physical warm-up) at the beginning, in the middle, and at the end of the season. The findings suggest that a mental warm-up is both acceptable to athletes and potentially useful in helping them prepare for training and competition.